(untitled) (Revista de Estudos da Linguagem, 2007)
Bringing into scene the theoretical route followed by The ObrigatoryContour Principle (OCP), Kaingáng; Parkatêjê; Je languages; Tonallanguages, the present article has, among its aims: to contribute tothe determination of the nature of such principle and to get evidencefor a possible parameterization of it. In order to do so, we, based onspecific phonological apects of some languages (genetically relatedor not) spoken in Brasil, will investigate them from the point of viewof two interrelated theoretical questions which are still accepted,even in a representational model, and which refer to OCP evaluationalcontexts and its weakening from certain distances. The conclusionsreached here allow us to sustain the hypothesis that the nature ofOCP is linked to features involving articulation and perception. Theyalso allow us to suggest that the OCP can be parameterized: its evaluationcontexts can be minimally altered, according to the language, and itsapplication is not affected by other restrictions with which it interacts.